The identity of Calliphora bezzii Zumpt, 1956 (Diptera, Calliphoridae) - Rognes, Knut (Zootaxa, 2016)
The holotype male of a nominal species described from Italy, Calliphora bezzii Zumpt, 1956, including a microscope slide of its terminalia, was examined. The holotype is shown to belong to the Nearctic taxon Calliphora latifrons Hough, 1899. Thus, Calliphora bezzii is a junior synonym of C. latifrons, syn. nov.